P-Bar: Peanut-Based Snack Bar Innovation as Nutritious Food and Entrepreneurial Opportunity - Dewi Handayani; Triana Krisandini; Ayu Suci Lestari; Janisa Dwi Kurnia; Sefti Dahnia (Salus Publica: Journal of Community Service, 2026)
Indonesia has great potential in developing nutritious local foods, one of which is peanuts which are rich in protein and healthy fats. This study aims to develop "P-Bar" as a peanut-based snack bar that has the potential to be a nutritious food as well as an entrepreneurial opportunity based on local ingredients. The study used participatory study methods and literature studies through product manufacturing, promotion, and sales activities. P-Bar is made using the main ingredient of peanuts combined with powdered milk, margarine, sugar, eggs, and wheat flour. The protein and healthy fat content in peanuts make P-Bar a potential nutritious snack and a practical source of energy for the body. Sales results showed that 45 pieces of the product were successfully sold with a total revenue of Rp270,000 and a profit of Rp170,000 from a production capital of Rp100,000. These results indicate that P-Bar has the potential to be developed as a local food product with economic value and support the development of local food-based entrepreneurship.